Co-emergence Reinforcement and Its Relevance to Interoceptive Desensitization in Mindfulness and Therapies Aiming at Transdiagnostic Efficacy - Cayoun, Bruno A.; Shires, Alice G. (Frontiers in Psychology, 2020)
Interoception, the ability to feel the body’s internal sensations, is an essential aspect of emotional experience. There is mounting evidence that interoception is impaired in common mental health disorders and that poor interoceptive awareness is a major contributor to emotional reactivity, calling for clinical interventions to address this deficit. The manuscript presents a comprehensive theoretical review, drawing on multidisciplinary findings to propose a metatheory of reinforcement mechanisms applicable across a wide range of disorders. We present a reconsideration of operant conditioning through the co-emergence model of reinforcement, which is a neurophenomenological account of the interaction between cognition and interoception, and its consequences on behavior. The model suggests that during memory processing, the retrieval of autobiographical memory (including maladaptive cognition) is dependent upon its co-emerging interoceptive cues occurring at the encoding, consolidation and reconsolidation stages. Accordingly, “interoceptive reinforcement” during emotional distress is a common factor to all emotional disorders and a major cause for relapse. We propose that interoceptive desensitization has transdiagnostic benefits, readily achievable through the cultivation of equanimity during mindfulness training and can be integrated in cognitive and behavioral interventions to permit a transdiagnostic applicability. We summarize the contributions of this approach into 10 specific and testable propositions.